Estimation Of Aboveground Biomass And Carbon Storage In Pole And Tree Stands Several The Main Road Of Sumber Village, Surakarta - Aulia, Ahmad Asfar; Revalitha, Alya Adysti; Rahmania, Ardita (Universitas Pahlawan Tuanku Tambusai, 2024)
Vegetation absorb CO₂ and store it as biomass, thus contributing to climate change’s mitigation. This study aims to estimate the biomass of tree and pole stands on several main roads in Sumber Village, Surakarta and calculate their carbon stock. The research data included primary data (tree height, DBH, and species type) and secondary data from scientific literature. Measurements were made using non-destructive sampling method, and biomass was calculated using allometric formula, while carbon stock was 50% of tree biomass. Results showed there were 15 tree species and 12 pole species. The highest biomass and carbon stock were found in the third site (302.6 Ton/ha and 151.3 Ton/ha) and the lowest in the first site (210.94 Ton/ha and 105.7 Ton/ha). The potential of pole and tree stands along the main road in Sumber Village shows the importance of good green area management in urban areas in balancing the ecosystem.